MONOSODIUM GLUTAMATE POTENTIATES THE CONTRACTION OF THE VISCERAL SMOOTH MUSCLE OF DUODENUM BY AUGMENTING THE ACTIVITY OF INTRINSIC CHOLINERGIC EFFERENTS, INDUCING OXIDATIVE STRESS AND PROLIFERATING SMOOTH MUSCLE CELLS - SURAIYA PARVIN; PARTHA PRATIM NATH; MOUSUMI DUTTA; MUKTI MONDAL; ASHMA KHATUN; SANGHAMITRA PAL; MAHUA GUHA ROY; GOUTAM PAUL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to examine the effects of monosodium glutamate (MSG) on the contraction of visceral smooth muscle (VSM) of the duodenum in a rat model to understand the MSG-induced impairment of the function of the small intestine. Methods: Male albino rats of Charles Foster strain were exposed with MSG at three different dosages (632, 1264, and 2528 mg/kg BW/day) for 30-day duration. The records of the contraction of the duodenum were achieved with isotonic transducer (IT-2245) coupled with RMS-Polyrite D by our standard laboratory protocol. Results: We have observed potentiation of contraction of duodenum ex vivo dose-dependently in MSG exposed groups of rats compared to control. Furthermore, the enzymatic activity of acetylcholinesterase (AChE) in VSM tissue homogenate and expression of AChE protein in fixed duodenal muscle cell layers have been decreased in a dosage response manner comparing to control rats. We have found a significant decrease in the activities of some antioxidant enzymes such as Cu-Zn superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, glutathione-s-transferase, and increase in the level of malondialdehyde in MSG exposed VSM tissue homogenate of the duodenum. We have also observed thickening of muscularis externa layer and increase in the number of muscle cells in circular and longitudinal muscle layers of the duodenal wall in transverse duodenal wall sections stained with eosin-hematoxylin. Conclusion: MSG potentiates the contraction of VSM of duodenum by augmenting the activity of intrinsic cholinergic efferents predominantly, and inducing oxidative stress and proliferating smooth muscle cells.